Three decades of international cooperation against corruption: looking ahead - Borlini, Leonardo S.; Peters, Anne (International journal of constitutional law, 2024)
Corruption, a ubiquitous phenomenon throughout history and societies, has been long criminalized in many countries. However, international cooperation against corruption only gained momentum in the 1990s. Since then, the international legal framework has expanded significantly through conventions like the Organisation on Economic Co-operation and Development (OECD) Anti-Bribery Convention and the UN Convention against Corruption. Nearly all states have now ratified at least one anticorruption treaty. However, implementation and enforcement of these standards has been uneven across states. Domestic reforms have also lagged in some areas like prevention. Corruption remains widespread, and its socioeconomic costs have not appreciably decreased. This Symposium aims at assessing the outcomes of three decades of international cooperation in combating corruption, while also exploring the future directions of international anticorruption rules and cooperation. Through a positive, critical, and normative legal analysis, complemented by empirical research and behavioral science, it focuses on the dynamic interactions between international anticorruption instruments and municipal law, highlighting understudied problems, both substantive and methodological. After discussing the origins and evolution of international anticorruption law, this introductory article presents the state of the art on the questions tackled by this Symposium and highlights its contribution to existing literature on the topic. In doing so, it brings together various trends emerging from the articles contained in this Symposium and explores avenues for further research and reflection.